Rekonstruksi Pendidikan Islam Melalui Gerakan Modernisme Muhammadiyah - Siti Zakia Fuadatinnur; M. Syahrudini (Al-Kindi, 2025)
Islamic education is currently facing increasingly complex challenges due to rapid technological advancement, social transformation, and the growing demands of 21st-century competencies. These conditions require a comprehensive reconstruction that goes beyond technical improvements in learning and encompasses deeper shifts in educational paradigms, epistemology, and institutional governance. This study aims to analyze the principles of Muhammadiyah modernism as a conceptual foundation for developing a more relevant and progressive model of Islamic education reconstruction. The research employs a library-based qualitative approach by examining literature on Islamic modernism, the thoughts of K.H. Ahmad Dahlan, and the Muhammadiyah educational system. The findings reveal that Muhammadiyah modernism grounded in the pillars of purification of teachings, rationality, and openness to science provides an integrative, adaptive, and forward-looking educational framework. The integration of religious and general sciences, the implementation of active learning models, and the professionalization of educational management serve as key strengths in this transformative effort. These findings affirm that Muhammadiyah modernism can function as a strategic paradigm for reconstructing Islamic education, enhancing its relevance, quality, and competitiveness in the modern era.